Effects of stepping-in-place tempo and type of roundhouse kick on coincidence-anticipation timing in Taekwondo - Lee, J.; Park, I. (International Journal of Performance Analysis in Sport, 2022)
The aims of this study were to examine the effects of stepping-in-place tempo on coincidence-anticipation timing (CAT) performance of roundhouse kick and to determine whether the CAT performance was the same according to types of roundhouse kick. Fifteen Taekwondo experts performed four different type of roundhouse kicks at three different stepping-in-place tempos (120, 140, and 160 bpm) in two stimulus speeds conditions for CAT performance. Raw scores were transformed to three error scores; constant, absolute, and variable errors and were analysed using separate 2 (stimulus speeds) x 4 (kick types) x 3 (tempos) repeated measures of analyses of variance. In the results, error scores (CE and AE) were significantly lower at 140 and 160 bpm compared to that at 120 bpm. Significant differences according to stepping-in-place tempo were also evident in the type of kicks (front leg < rear leg and body < head). The error scores were found to increase as the stimulus speed increased (10 mph < 20 mph) and were lower at 140 bpm compared to 120 and 160 bpm at both stimulus speed. Regardless of the type of kicks and stimulus speed, the lowest variable error was found at 140 bpm.